HUKUM, HAKIM, MAHKUM FIH DAN MAHKUM ALAIH (Studi Pemahaman Dasar Ilmu Hukum Islam) - Cut Ali, Isnu (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Agama Islam Jamiatut Tarbiyah Lhoksukon, 2021)
In the terms of the ushul scholars, law is defined as a khitabsyari 'which is related to the actions of mukallaf, whether they are thalab (demands), takhyiir (choice) or wadl'i (provisions). Meanwhile, law according to fiqh experts is a syar'i characteristic which is the influence of the khitab. Thus, the influence of Allah's khitab which implies the obligation to perform prayers from the verse